Synthesis and docking studies of pyrazine-thiazolidinone hybrid scaffold targeting dormant tuberculosis - Chitre, T. S.; Asgaonkar, K. D.; Miniyar, P. B.; Dharme, A. B.; Arkile, Manisha A.; Yeware, A.; Sarkar, Dhiman; Khedkar, Vijay M.; Jha, Prakash C. (Bioorganic & Medicinal Chemistry Letters, 2016)
The persistence of Mycobacterium tuberculosis (MTB) in dormant stage assists the pathogen to develop resistance against current antimycobactrial drugs. To address this issue, we report herein the synthesis of N-(4-oxo-2 substituted thiazolidin-3yl) pyrazine-2-carbohydrazide derivatives designed by following the molecular hybridization approach using pyrazine and thiazolidenone scaffolds. The compounds were evaluated against MTB H37Ra and Mycobacterium bovis BCG in dormancy model. Most of the compounds had IC50 values in 0.3-1 mu g/ml range. The active compounds were further tested for anti-proliferative activity against THP-1, Panc-1, A549, and MCF-7 cell lines using MTT assay and exhibited no significant cytotoxicity. We also report molecular docking studies using active analogs and MTB Decaprenylphosphoryl-beta-D-ribose-2'-epimerase (DprE1) to rationalize the biological activity and to provide an insight into the probable mechanism of action and binding mode of hybridized structures. The results obtained validate the use of molecular hybridization approach and also suggest that reported compounds can provide a novel pharmacophore to synthesize lead compounds against dormat MTB. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: docking; Dormant; Hybrid design; Pyrazine; Thiazolidenone; tuberculosis